Pendidikan Karakter Dalam Pembelajaran Bahasa Jepang Pada Mahasiswa Pariwisata - Alvira, Idea; Victory, Well; Eliza, Meria (Journal of Tourism Sciences, Technology and Industry, 2024)
Character education is a form of instilling noble values and goodness. In practice, character education requires time and a long process in order to produce someone with noble morals. The strong character of the Indonesian nation will make this nation dignified and respected by other nations. This is our common goal and dream. Through the younger generation, especially pupils and students, Indonesia's future is at stake. Not only in school, in the world of higher education, character education can also be integrated into classroom learning. This paper uses a qualitative data type approach with descriptive methods, describes how Japanese language learning for tourism students takes place accompanied by the cultivation of noble culture and good values of Japanese society. This is in accordance with the character education values that have been prepared by the Department of National Education, these include religious values, friendship/ communicativeness, love of peace, social care, responsibility and discipline. As part of national education goals, it is hoped that these values can be absorbed and implemented in everyday life.